2013
DOI: 10.1038/bjc.2013.544
|View full text |Cite
|
Sign up to set email alerts
|

The association between different night shiftwork factors and breast cancer: a case–control study

Abstract: Background:Research on the possible association between shiftwork and breast cancer is complicated because there are many different shiftwork factors, which might be involved including: light at night, phase shift, sleep disruption and changes in lifestyle factors while on shiftwork (diet, physical activity, alcohol intake and low sun exposure).Methods:We conducted a population-based case–control study in Western Australia from 2009 to 2011 with 1205 incident breast cancer cases and 1789 frequency age-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 40 publications
5
86
0
2
Order By: Relevance
“…We could not corroborate a short-term effect of night shift work on the risk of breast cancer as suggested by experimental data (10,16). This finding is consistent with that of Fritschi et al (20) and Pesch et al (18) who observed no elevated risk among women working night shifts within the recent ten years [odds ratios (OR) 1.02, 95% CI 0.73-1.43 and 1.04, 95% CI 0.31-3.53, respectively]. However, our findings are not consistent with the findings of Davis et al who observed a slightly elevated risk during the recent ten years of night shift work (OR 1.6, 95% CI 1.0-2.5) (19).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We could not corroborate a short-term effect of night shift work on the risk of breast cancer as suggested by experimental data (10,16). This finding is consistent with that of Fritschi et al (20) and Pesch et al (18) who observed no elevated risk among women working night shifts within the recent ten years [odds ratios (OR) 1.02, 95% CI 0.73-1.43 and 1.04, 95% CI 0.31-3.53, respectively]. However, our findings are not consistent with the findings of Davis et al who observed a slightly elevated risk during the recent ten years of night shift work (OR 1.6, 95% CI 1.0-2.5) (19).…”
Section: Discussionsupporting
confidence: 48%
“…Of the several epidemiologic studies conducted, only three studies have examined possible short-term risk of recent night shift work (18)(19)(20). Davis et al observed an increased risk of breast cancer among women who ever worked the graveyard shift during the last ten years (19).…”
mentioning
confidence: 99%
“…However, some other studies failed to establish a clear association [161]. This case-control study evaluated the association between variant night shift factor and breast cancer incidences in Western Australia using a self-administered questionnaire and telephone interview to obtain details about demography, lifestyle, occupational history, and shift work factors, including ALAN, phase shift, and sleep duration [161]. In this study, night shift has been found to be associated with a small but statistically significant increase risk for breast cancer, but the association with other shift work factors, such as duration of exposure to ALAN and sleep disturbance, showed inconsistent results.…”
Section: Circadian Disruption and Breast Cancermentioning
confidence: 99%
“…Most of the epidemiological and experimental data provide a well-established association between circadian disruption by shift work, ALAN, and breast cancer risk. However, some other studies failed to establish a clear association [161]. This case-control study evaluated the association between variant night shift factor and breast cancer incidences in Western Australia using a self-administered questionnaire and telephone interview to obtain details about demography, lifestyle, occupational history, and shift work factors, including ALAN, phase shift, and sleep duration [161].…”
Section: Circadian Disruption and Breast Cancermentioning
confidence: 99%
“…Studies on breast cancer that have accounted for sun exposure in their analyses reported only marginal changes in their night work risk estimates. 4,5 The role of sunlight exposure and vitamin D has been long debated and the evidence from observational studies, on levels of serum 25-hydroxyvitamin D and incidence of prostate cancer is inconclusive.…”
mentioning
confidence: 99%